E eu gosto de homens e de mulheres e você o que prefere? : a influência dos discursos sócio-históricos no ato de assumir a bissexualidade - Trevisol, Bibiane (2025)
This doctoral thesis addresses the influence of socio-historical discourses on the acceptance of bisexuality. More specifically, the research sought to understand the factors involved in the process of coming out — or not — as bisexual across different periods, taking into account the socio-historical discourses that have influenced individuals’ choices. This is a field research and case study conducted through semi-structured interviews with bisexual individuals born between 1960 and 2000. The analysis is based on the principles of the Discursive Semiotics (Greimas & Courtés, 2013; Fiorin, 2000), examining the levels of the generative path of meaning of the interviews and engaging with authors who theorize discourse, ideology, and identity (Fiorin, 1998, 1999; Landowski, 2012), as well as concepts related to bisexuality and prejudice (Angelides, 2001; Sullivan, 2003; Barros, 2011). We conclude that the more temporally distant the historical window, the greater the influence of socio-historical discourses on individuals, leading them to conceal their self-recognition and their bisexuality, even when engaging in bisexual behaviors. The results indicate the interference of the heteronormative family and the religious beliefs adopted by their social group as relevant factors for the individuals. Moreover, the findings reveal a greater openness in more recent decades, which is associated with the struggles of the LGBTQIAPN+ movement. Additionally, they point to a certain “invisibility” of bisexual individuals both within the movement and in society.